PENGARUH TECHNOLOGY ACCEPTANCE MODEL TERHADAP MINAT PENGGUNAAN E-PAYMENT SEBAGAI ALAT PEMBAYARAN PADA DAPUR NUSANTARA - Kevin Julianto Singgih; Yoseva Maria (Universitas Ciputra Surabaya, 2021)
Abstract: The development of technology keeps increasing, one of them is information technology and communication. One of the technology development forms is smartphone. E-Payment is one of the technology features that is accessible in smartphone that is used as a payment tool. The use of E-Payment at Dapur Nusantara has been on going for a year and it keeps being used especially in the midst of this pandemic time. Dapur Nusantara is a business that runs in food field and it sells nusantara specialty products that are instantly wrapped, one of them is burger krawu, and it evolves sells product like rice bowl with Indonesian typical dish. Technology Acceptance Model (TAM) is used to analyze and understand the factors that affect the acceptance of technology. The purpose of this research is to find out the effect of (1) perceived usefulness on e-payment use interest (2) perceived ease of use on e-payment use interest (3) perceived benefits of e-payment use interest as payment tool at Dapur Nusantara. This research uses descriptive quantitative method by distributing questionnaire way to 80 respondents with criteria that has been provided, that is, the consumers of Dapur Nusantara. The analysis tool that is used is SPSS. The result of this research is (1) perceived usefulness does not affect on e-payment use interest in using e-payments (2) perceived ease of use affects e-payment use interest (3) perceived benefits affect on e-payment use interest as a payment tool of Dapur Nusantara. Keywords: Dapur Nusantara, Technology Acceptance Model, perceived usefulness, perceived ease of use, perceived benefits, interest in use.